Synthesis and Characterization of Nanocrystalline YSZ Powder by Smoldering Combustion Synthesis. (2006) - Kaus, Ingeborg; Dahl, Paul Inge; Mastin, Johann; Grande, Tor; Einarsrud, Mari-Ann
Abstract : Nanocrystalline yttria-stabilized zirconia (YSZ) powders with 8 mol% Y2 O3 have been produced using smoldering combustion synthesis with glycine as fuel and nitrate as oxidizer. The YSZ powders prepared by using different glycine to nitrate ratios (0.20–1.0) have been characterized by X-ray diffraction (crystallite size), thermogravimetry, infrared spectroscopy, surface area analysis, transmission electron microscopy, and dilatometry to determine the parameters giving the powder the best properties when it comes to densification properties. The influence of calcination temperature on crystallite size, surface area, and carbonate species remaining from the smoldering combustion reaction has been studied especially for the G/N ratio of 0.23 to reveal the optimal synthesis conditions. A G/N ratio of 0.23 and calcination in the range 650–900 º C in oxygen flow gave high quality powder with a crystallite size less than 10 nm. Densities of sintered bodies exhibit an increase for calcination temperatures above 600 º C, where most of the residual carbonate species has been removed.